IMPROVING MENARCHE READINESS THROUGH HEALTH EDUCATION FOR YOUNG WOMEN - Etika Purnama Sari (Journal of Health Community Service, 2021)
Many young women are not ready to menarche. Young women need information about the menstrual process and health during menstruation so as not to have difficulty in dealing with menarche. Health education intended for Young Women (women aged 9-13 years) who have not experienced menarche in RT 10 RW 4 Kel. Latsari Kec. Banjar Tuban as many as 10 people. The method of health education is to talk online using zoom meetings, educational media is leaflet and media evaluation of readiness to face menarche is questionnaire. Most respondents (80%) not ready to face menarche before health education and most respondents (70%) ready to face menarche after health education. Health education can improve readiness to face menarche for young women. In addition to health education other factors that can also affect the readiness to face menarche is age and information sources. Young women are expected to find information related to menarche through family, peers, school or through social media to improve menarche readiness.